THE EFFECT OF VOICE OF AMERICA (VOA) APPLICATION ON STUDENTS’ READING COMPREHENSION OF TENTH GRADE OF SMK PUTRA ANDA BINJAI STUDENTS - Nudia Yultisa; Yulinda Dwinata; Winda Lestari; Ummi Umara (PT. Radja Intercontinental Publishing, 2020)
This study aimed to find out whether using VOA application affects students’ reading comprehension of the tenth grade students of SMK Putra Anda Binjai. In this study, using VOA application as the independent variable (X) and students’ reading comprehension as the dependent variable (Y), The population of this study is the all of tenth grade students of SMK Putra Anda Binjai. The sample was taken by using random sampling, that consist of 56 students. Then, the sample was divided into two groups, the group taught by using VOA application as the experimental group and the group taught without VOA application is the control group. The writer uses multiple choice test as the instrument of collecting data. The data analyzed by using t-test formula. The high score of pre test in control group the students got 80, and for post test the students got 90, while the low score of the pre test the students got 50, and for post test the students got 60. The high score of pre test in experimental group the students got 85, and for post test the students got 90 while the low score the students got 65 and for pre test the students got 60. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table, (tobserved = 2,19 > ttable = 1,674). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using VOA application affects the students’ reading comprehension of tenth grade students of SMK Putra Anda Binjai.